Effective determination of cyclic-visco-plasticity material properties using an optimisation procedure and experimental data exhibiting scatter - Rouse, James Paul; Hyde, Christopher J.; Sun, W.; Hyde, T.H. (Taylor & Francis, 2014)
It may be inevitable in the design and analysis of most high temperature components (such as power industry pipe work) that variations in load and/or temperature will occur in normal operation. This presents complications in the prediction of the response of such components due to potential hardening or softening effects caused by the accumulation of plastic strain. Furthermore, interactions between hardening (or softening) behaviour and creep may be observed, particularly in high temperature applications. In this paper, the Chaboche model is described as it has the potential to represent this type of behaviour. An optimisation procedure for fine tuning material constants is developed and presented. This is a key step as the determination of initial estimates requires several assumptions to be made. Several potential pitfalls in optimisation procedures are described and addressed, mainly through the application of experimental data cleaning as a pre-processing procedure. This removes unavoidable experimental scatter that inhibits optimisation. Investigations into the effects of variations in the initial conditions on optimised material constant values and the number of data points selected on computational times are made to aid in the application of similar optimisation procedures. The superior fitting given by the implementation of an optimisation procedure is verified by applying it to the results of strain controlled cyclic tests of a P91 steel at 600°C.